Civic Engagement as an Avenue to Interreligious Cooperation in Religiously Diverse Communities - Waters, Mark (Journal of ecumenical studies, 2018)
This essay identifies sociological research in India and in the United States indicating that positive interreligious engagement reduces the risk of violence, increases peaceful civic interaction, and builds civic cooperation in religiously plural environments. The research presented analyzes circumstances and relationships in settings that are characterized by peaceful interreligious interaction. In the essay, warrant is suggested for moving beyond description to prescription. Seeking to create opportunities for interreligious engagement in associational and quotidian civic relationships is one means of fostering interreligious cooperation, even among people who have no expressed interest in religious literacy or formal interreligious dialogue.